Relationship between knee joint discomfort, self-management behavior, and quality of life in the middle-aged and elderly people in China: A cross-sectional study - Su, Manman; Zhou, Yang; Zhao, Peipei; Zeng, Biyun; Zhou, Qidi (Frontiers in Public Health, 2022)
Background: To describe knee joint discomfort, self-management behavior and quality of life (QoL) in the middle-aged and elderly in China and clarify the relationship between them. Methods: A cross-sectional study and stratified multi-stage random sampling method was used to collect data on knee joint discomfort, self-management behavior and QoL among middle-aged and elderly people in Hunan province. Spearman's correlation analysis was used to test the relationship. Results: Among them, the prevalence of knee pain was the highest (52.1%), followed by knee weakness (42.5%), numbness (41.8%), cold feeling (40.0%), tenderness (38.3%) and distension feeling (37.5%). Average score of self-management of knee joint discomfort in middle-aged and elderly people was 2.14 ± 0.67. The level of self-management in each dimension ranged from high to low as emotional management, daily management, symptom management and information management. The average score of physical component summary (PCS) and mental component summary (MCS) was 42.85 ± 5.34 and 43.62 ± 8.43 respectively. The occurrence, frequency and severity of discomfort symptoms were positively correlated with the symptom management, daily management, information management, and self-management behaviors, and negatively correlated with emotional management，PCS and MSC except for the occurrence of discomfort symptoms (P < 0.05). Conclusion: Knee joint discomfort was prevalent in middle-aged and elderly people. In addition, they had a low level of self-management behavior and poor QoL. The middle-aged and elderly had knee discomfort symptoms, the more frequent and severe symptoms, the higher level of symptom management, daily management and information management, and the lower level in emotional management and QoL.